2013
DOI: 10.1111/trf.12264
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐specific red blood cell storage, metabolism, and eicosanoid generation in a mouse model

Abstract: Background RBC transfusion is a life-saving therapy, the logistical implementation of which requires RBC storage. However, stored RBCs exhibit substantial donor variability in multiple characteristics, including hemolysis in vitro and RBC recovery in vivo. The basis of donor variability is poorly understood. Study Design and Methods We applied a murine model of RBC storage and transfusion to test the hypothesis that genetically distinct inbred strains of mice would demonstrate strain-specific differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
102
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(110 citation statements)
references
References 29 publications
8
102
0
Order By: Relevance
“…We previously utilized this model to identify metabolic patterns that correlated with good storage (RBCs from C57BL/6 mice) or poor storage (RBCs from FVB mice) [70]. Since the present data utilized the same analysis platform, we can compare the murine results with metabolic changes of human RBCs stored in AS-1.…”
Section: Discussionmentioning
confidence: 99%
“…We previously utilized this model to identify metabolic patterns that correlated with good storage (RBCs from C57BL/6 mice) or poor storage (RBCs from FVB mice) [70]. Since the present data utilized the same analysis platform, we can compare the murine results with metabolic changes of human RBCs stored in AS-1.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, the same lipid oxidation pathways are associated with poor storage. 29 In addition, dicarboxylic acids remain associated with poor storage in leukoreduced RBCs (data not shown). Thus, while some of the associated change may be due to contaminating leukocytes and/or platelets, the major findings of lipid peroxidation persist even with leukoreduction.…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinical consequences of such differences have not been established in humans, studies in mice have demonstrated strain-specific susceptibility to RBC injury from cold storage that correlates with posttransfusion RBC recovery and function. 8,9 …”
Section: Introductionmentioning
confidence: 99%